Glucose intolerance induced by blockade of central FGF receptors is linked to an acute stress response - Jennifer M. Rojas; Miles E. Matsen; Thomas O. Mundinger; Gregory J. Morton; Darko Stefanovski; Richard N. Bergman; Karl J. Kaiyala; Gerald J. Taborsky Jr; Michael W. Schwartz (Elsevier, 2015)
Objective: Central administration of ligands for fibroblast growth factor receptors (FGFRs) such as fibroblast growth factor-19 (FGF19) and FGF21 exert glucose-lowering effects in rodent models of obesity and type 2 diabetes (T2D). Conversely, intracerebroventricular (icv) administration of the non-selective FGFR inhibitor (FGFRi) PD173074 causes glucose intolerance, implying a physiological role for neuronal FGFR signaling in glucose homeostasis. The current studies were undertaken to identify neuroendocrine mechanisms underlying the glucose intolerance induced by pharmacological blockade of central FGFRs. Methods: Overnight fasted, lean, male, Long-Evans rats received icv injections of either PD173074 or vehicle (Veh) followed 30 min later by performance of a frequently sampled intravenous glucose tolerance test (FSIGT). Minimal model analysis of glucose and insulin data from the FSIGT was performed to estimate insulin-dependent and insulin-independent components of glucose disposal. Plasma levels of lactate, glucagon, corticosterone, non-esterified free fatty acids (NEFA) and catecholamines were measured before and after intravenous (iv) glucose injection. Results: Within 20 min of icv PD173074 injection (prior to the FSIGT), plasma levels of lactate, norepinephrine and epinephrine increased markedly, and each returned to baseline rapidly (within 8 min) following the iv glucose bolus. In contrast, plasma glucagon levels were not altered by icv FGFRi at either time point. Consistent with a previous report, glucose tolerance was impaired following icv PD173074 compared to Veh injection and, based on minimal model analysis of FSIGT data, this effect was attributable to reductions of both insulin secretion and the basal insulin effect (BIE), consistent with the inhibitory effect of catecholamines on pancreatic β-cell secretion. By comparison, there were no changes in glucose effectiveness at zero insulin (GEZI) or the insulin sensitivity index (SI). To determine if iv glucose (given during the FSIGT) contributed to the rapid resolution of the sympathoadrenal response induced by icv FGFRi, we performed an additional study comparing groups that received iv saline or iv glucose 30 min after icv FGFRi. Our finding that elevated plasma catecholamine levels returned rapidly to baseline irrespective of whether rats subsequently received an iv bolus of saline or glucose indicates that the rapid reversal of sympathoadrenal activation following icv FGFRi was unrelated to the subsequent glucose bolus. Conclusions: The effect of acute inhibition of central FGFR signaling to impair glucose tolerance likely involves a stress response associated with pronounced, but transient, sympathoadrenal activation and an associated reduction of insulin secretion. Whether this effect is a true consequence of FGFR blockade or involves an off-target effect of the FGFR inhibitor requires additional study.